2010
DOI: 10.1038/sj.bjc.6606052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA-A2-restricted CTL epitopes of a novel tumour-associated antigen, KIF20A, overexpressed in pancreatic cancer

Abstract: Background:Identification of tumour-associated antigens (TAAs) that induce cytotoxic T lymphocytes (CTLs) specific to cancer cells is critical for the development of anticancer immunotherapy. In this study, we aimed at identifying a novel TAA of pancreatic cancer for immunotherapy.Methods:On the basis of the genome-wide cDNA microarray analysis, we focused on KIF20A (also known as RAB6KIFL/MKlp2) as a candidate TAA in pancreatic cancer cells. The HLA-A2 (A*02:01)-restricted CTL epitopes of KIF20A were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 31 publications
2
66
0
Order By: Relevance
“…Immunohistochemical staining of KIF20A using a rabbit polyclonal antibody against KIF20A (A300-879A, Bethyl Laboratories) was conducted as described previously (1,2,27 Peptide-stimulated degranulation of CD4 þ T lymphocytes was determined by flow cytometric analysis of CD107a exposed on the cell surface as described previously, with some modifications (28). Detailed methods are provided in Supplementary Materials and Methods.…”
Section: Immunohistochemical Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical staining of KIF20A using a rabbit polyclonal antibody against KIF20A (A300-879A, Bethyl Laboratories) was conducted as described previously (1,2,27 Peptide-stimulated degranulation of CD4 þ T lymphocytes was determined by flow cytometric analysis of CD107a exposed on the cell surface as described previously, with some modifications (28). Detailed methods are provided in Supplementary Materials and Methods.…”
Section: Immunohistochemical Examinationmentioning
confidence: 99%
“…KIF20A has been reported to be a promising immunotherapeutic target for cancers. Studies have reported that 2 short peptides (SP) derived from KIF20A, KIF20A-A2 , and KIF20A-A24 66-75 stimulated CTLs, which kill cancer cells endogenously expressing KIF20A antigen and that KIF20A-specific CTLs were present in peripheral blood mononuclear cells (PBMC) obtained from patients with pancreatic cancer (1,4). Phase I/II clinical trials of cancer immunotherapy for lung cancer, pancreatic cancer, and cholangiocellular carcinoma using KIF20A-derived SP are underway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTAs are restricted in normal tissues to germ cells of the testis, with occasional expression in female reproductive organs, and are expressed in histologically different types of malignant human tumors [1][2][3][4]. The tumor restricted expression pattern of CTAs makes them an interesting target for immunotherapeutic approaches [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…SEREX was not limited to immunogenic cancers such as melanoma and has now been used to identify more than 2,000 antigens [22][23] in a large range of different solid [24][25][26] and haematological malignancies [27][28][29][30]. cDNA libraries are created from tumour samples, cell lines or healthy normal donor cells (such as testes).…”
Section: Serological Identification Of Antigens By Recombinant Expresmentioning
confidence: 99%